2018
DOI: 10.1016/j.bbmt.2018.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Donor Cell–Derived Hematologic Neoplasms after Hematopoietic Stem Cell Transplantation: A Systematic Review

Abstract: Development of de novo hematologic malignancies in donor cells after allogeneic stem cell transplantation (allo-SCT) provides a useful in vivo model to study the process of leukemogenesis. A systematic analysis of the cases reported in the literature was performed to identify risk factors and mechanisms involved in the pathogenesis of donor cell-derived hematologic neoplasms (DCHN) and leukemogenic transformation. Relevant data were extracted from 137 cases. Cases of DCHN show a wide heterogeneity with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…However, despite MRD analyses being more specific than chimerism analyses, they can fail to detect relapse when expression of surface or molecular markers is lost due to clonal heterogeneity, which is not uncommon. Moreover, in the rare situation of donor cell leukemia [46][47][48], the presence of leukemic cells can be misdiagnosed as disease relapse if chimerism analysis is not performed. Therefore, we consider that monthly chimerism follow-up should be performed in unseparated PB in acute leukemia patients during the first year after HSCT and every three months during the second year.…”
Section: Methodological Algorithm For Quantitative Chimerism Follow-upmentioning
confidence: 99%
“…However, despite MRD analyses being more specific than chimerism analyses, they can fail to detect relapse when expression of surface or molecular markers is lost due to clonal heterogeneity, which is not uncommon. Moreover, in the rare situation of donor cell leukemia [46][47][48], the presence of leukemic cells can be misdiagnosed as disease relapse if chimerism analysis is not performed. Therefore, we consider that monthly chimerism follow-up should be performed in unseparated PB in acute leukemia patients during the first year after HSCT and every three months during the second year.…”
Section: Methodological Algorithm For Quantitative Chimerism Follow-upmentioning
confidence: 99%
“…7 Review of the literature identified more than 70 cases of AML DCL (Table S1). 8 The Figure 3). Another study reported that DCL appears earlier in patients transplanted with CB.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature identified more than 70 cases of AML DCL (Table ) . The median time between allogenic HSCT and occurrence of AML DCL was 30 months (range 1‐279).…”
Section: Discussionmentioning
confidence: 99%
“…Donor-derived leukemia (DDL) is a severe complication of HSCT in which patients later develop a secondary leukemia of donor origin ( Fialkow et al., 1971 ; Wiseman, 2011 ). Previously considered rare, DDL mayconstitute 5% or more of leukemia relapses, and the number of cases has continued to increase over the last 50 years, particularly since 2000 ( Suarez-Gonzalez et al., 2018a ; Wiseman, 2011 ). The median age of recipients with DDL ranges from 31 to 53 years, indicating that it may be more common in adults ( Suarez-Gonzalez et al., 2018a ; Wang et al., 2011 ; Wiseman, 2011 ).…”
Section: Main Textmentioning
confidence: 99%